Importance of Iron Absorption in Human Health: An Overview - Dixit, Satya P.; Rajan, Logesh; Palaniswamy, Dhanabal; Mohankumar, Suresh K. (Current Nutrition & Food Science, 2021)
Iron is one of the essential elements required for human health, as it plays a vital role in a number of metabolic, growth, and developmental processes, including erythropoiesis, DNA synthesis, electron transport, and others. Iron deficiency is a concern in both developing and developed (industrialized) countries, and, in particular, young women are highly vulnerable. This review investigates the dietary and genetic determinants of iron metabolism in the human body and a possible solution to combat iron deficiency by exploring various targets. Hence, this review mainly focuses on the assessment of dietary and genetic factors affecting the iron bioavailability and homeostasis and collates the available information from 2000 to till date from the Pubmed database. The dietary factors, including ascorbic acid, an important factor in animal protein foods (meat, fish, and poultry), enhance iron absorption whereas the phytic acid, soy protein, calcium, and polyphenols have been reported to inhibit iron absorption. However, the effects of these dietary factors on iron absorption do not necessarily translate into an association with iron status and iron stores (serum ferritin concentration). Moreover, the genetic factors influence the absorption of iron involving HFE, TFR2, FPN1, and HAMP in humans. Further research is needed to determine optimal dietary recommendations for both the prevention and treatment of iron deficiency.
Keywords: phytic acid